Undergraduate University of the Philippines Diliman BLIS students' perceptions of the advantages and disadvantages of implementing an electronic security system at the ILIS Library - Irinco, Reila Anasol R.; Jamin, Raymond P. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
This study, in improvising the security at the library of ILIS, attempted to determine if there is a need to install an electronic security system and the perceived advantages and disadvantages of installing an electronic security system in the library. This research used a survey questionnaire as a means to gather data. The researcher used Slovin's Formula to determine the sample size of the population. Two hundred nineteen (219) out of four hundred eighty eight (488) answered the questionnaire and these are undergraduate UP Diliman BLIS students.
This study discussed the security as a problem at the ILIS Library. Students identified problems regarding security at the library. Questions focused particularly on the implementation of electronic security system and the advantages and disadvantages it provided.
The findings show that although security is not a problem at the library with a small population, an electronic security system is still required. Other benefits like efficiency, accuracy, speed, customization, staff satisfaction and better tracking were considered in implementing an electronic security system. This study paves the way for further studies that can help advance the current system at the ILIS Library.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Institute of Library and Information Science Library; Electronic security systems